STRUKTUR MODAL DITINJAU DARI STRUKTUR AKTIVA, UKURAN PERUSAHAAN, TINGKAT PERTUMBUHAN DAN RISIKO BISNIS - Deden Edwar Yokeu Bernardin; Fansury Abdillah (Jurnal Financia : Akuntansi dan Keuangan, 2022)
Capital structure as a balance between internal and external funds in a company. Optimal capital structure can reduce operating costs in the company. This study aims to analyze the effect of asset structure, firm size, growth rate and business risk on capital structure. The source of data in this study is secondary data in the form of quarterly financial statements of Perumda BPR BKPD Pangandaran for the 2011-2020 period. The population and sample in this study were 40 asset structure data, company size data, growth rate data, business risk data, and capital structure data for regional company BPR BKPD Pangandaran during the 2011-2020 period. The method in this study uses descriptive analysis and verification analysis. Verificative analysis. The results show that the asset structure, firm size, growth rate, and business risk have a significant effect on capital structure simultaneously, but the asset structure and growth partially become factors that have an insignificant influence.